2014
DOI: 10.1177/0300060514521153
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative haemodynamic changes in transplanted liver: Long-term follow-up with ultrasonography

Abstract: Objective: To investigate haemodynamic changes in the transplanted liver without postoperative complications. Methods: Colour Doppler ultrasound was used to monitor recipients of liver transplants who had no postoperative complications. The haemodynamic data for the hepatic vasculature were compared at different time-points during the first 4 years after liver transplantation. Results: A total of 144 liver transplant patients were enrolled in the study. Portal vein flow velocity decreased significantly from 72… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 27 publications
2
12
0
5
Order By: Relevance
“…7 1] cm/s at 1 month after transplant (P < .05). 3 In addition, in a series on 51 DDLT recipients, Stell and associates found that the mean portal venous flow decreased by approximately 20% in the first postoperative week. 1 Previous studies have reported marked hemodynamic changes after reperfusion of a partial graft in LDLT versus those occurring in DDLT.…”
Section: Omar Abdelaziz Et Al/experimental and Clinical Transplantatimentioning
confidence: 96%
See 4 more Smart Citations
“…7 1] cm/s at 1 month after transplant (P < .05). 3 In addition, in a series on 51 DDLT recipients, Stell and associates found that the mean portal venous flow decreased by approximately 20% in the first postoperative week. 1 Previous studies have reported marked hemodynamic changes after reperfusion of a partial graft in LDLT versus those occurring in DDLT.…”
Section: Omar Abdelaziz Et Al/experimental and Clinical Transplantatimentioning
confidence: 96%
“…Low HA RI can also be observed in other pathologic conditions, including HA stenosis, severe aorto-celiac athe rosclerotic disease, arteriovenous or arterial biliary fistula formation, and hepatic vein or portal vein thrombosis. 3 We observed an intraoperative elevation of HA PSV (range, 20-300 cm/s; mean [SD] of 96. 3 [65] cm/s) with significant decline in the first day after transplant without long-term consequences.…”
Section: Omar Abdelaziz Et Al/experimental and Clinical Transplantatimentioning
confidence: 96%
See 3 more Smart Citations